Effects of sodium butyrate on growth performance, antioxidant status, inflammatory response and resistance to hypoxic stress in juvenile largemouth bass (Micropterus salmoides) - Hou, Dongqiang; Li, Min; Li, Peijia; Chen, Bing; Huang, Wen; Guo, Hui; Cao, Junming; Zhao, Hongxia (Frontiers in Immunology, 2023)
The aim of this study was to investigate the effects of sodium butyrate (SB) supplementation on growth performance, antioxidant enzyme activities, inflammatory factors, and hypoxic stress in largemouth bass (Micropterus salmoides). Diets were supplemented with different doses of SB at 0 (SB0), 0.5 (SB1), 1.0 (SB2) and 2.0 (SB3) g/kg. The hypoxic stress experiment was performed after 56 days of culture. The results showed that compared with the SB0 group, the final body weight, weight gain rate and protein deposition rate of the SB3 group were significantly increased (P<0.05), while FCR was significantly decreased (P<0.05). The contents of dry matter, crude lipids, and ash in the SB2 group were significantly higher than those in the SB0 group (P<0.05).The urea level was significantly decreased (P<0.05), and the glucose content was significantly increased (P<0.05) in the SB supplement group. Compared with the SB0 group, the SB2 group had significant reductions in the levels of serum triglyceride, cholesterol, elevated-density lipoprotein cholesterol, and low-density lipoprotein (P<0.05), and significant reductions in the levels of liver alkaline phosphatase and malondialdehyde (P<0.05). The total antioxidant capacity of the SB1 group was higher than that of other groups (P<0.05). Compared with the SB0 group, the mRNA expression of TLR22, MyD88, TGF-β1, IL-1β and IL-8 in the SB2 group significantly decreased (P<0.05). The cumulative mortality rate was significantly decreased in the SB2 and SB3 groups in comparison with that in the SB0 group after three hours of hypoxic stress (P<0.05). In a 56-day feeding trial, SB enhanced largemouth bass growth by increasing antioxidant enzyme activity and inhibiting TLR22-MyD88 signaling, therefore increasing cumulative mortality from hypoxic stress in largemouth bass.